Influenza season 2016/17: Portugal - Rodrigues, Ana Paula (2018)
Influenza-like illness incidence rate; Influenza-like illness: medical appointments at primary health care; Laboratorial surveillance; Whole Genome Sequencing; Influenza cases in ICU.